Associates of Cardiopulmonary Arrest in the Perihemodialytic Period - Jennifer E. Flythe; Nien-Chen Li; Shu-Fang Lin; Steven M. Brunelli; Jeffrey Hymes; Eduardo Lacson (International Journal of Nephrology)
Cardiopulmonary arrest during and proximate to hemodialysis is rare but highly fatal. Studies have examined peridialytic sudden cardiac event risk factors, but no study has considered associates of cardiopulmonary arrests (fatal and nonfatal events including cardiac and respiratory causes). This study was designed to elucidate patient and procedural factors associated with peridialytic cardiopulmonary arrest. Data for this case-control study were taken from the hemodialysis population at Fresenius Medical Care, North America. 924 in-center cardiopulmonary events (cases) and 75,538 controls were identified. Cases and controls were 1 : 5 matched on age, sex, race, and diabetes. Predictors of cardiopulmonary arrest were considered for logistic model inclusion. Missed treatments due to hospitalization, lower body mass, coronary artery disease, heart failure, lower albumin and hemoglobin, lower dialysate potassium, higher serum calcium, greater erythropoietin stimulating agent dose, and normalized protein catabolic rate (J-shaped) were associated with peridialytic cardiopulmonary arrest. Of these, lower albumin, hemoglobin, and body mass index; higher erythropoietin stimulating agent dose; and greater missed sessions had the strongest associations with outcome. Patient health markers and procedural factors are associated with peridialytic cardiopulmonary arrest. In addition to optimizing nutritional status, it may be prudent to limit exposure to low dialysate potassium (<2 K bath) and to use the lowest effective erythropoietin stimulating agent dose.